Child Labor, School Attendance, and Intrahousehold Gender Bias in Brazil - Emerson, Patrick M.; Souza, André Portela (World Bank, 2012)
Child Labor, School Attendance, and Intrahousehold Gender Bias in Brazil Patrick M. Emerson and Andre Portela Souza An extensive survey data set of Brazilian households is used to test whether intrahousehold gender bias affects the decisions of mothers and fathers to send their sons and daughters to work and to school. An intrahousehold allocation model is examined in which fathers and mothers may affect the education investment and the child labor participation of their sons and daughters differently because of differences in parental preferences or differences in how additional schooling affects sons' and daughters' acquisition of human capital. The results suggest that fathers generally have a greater impact on decisions about sons and mothers generally have a greater impact on decisions about daughters. These results support models of intrahousehold bargaining in the child labor and schooling decisions of a family, even though most theoretical work on child labor has assumed a unitary family model. This study uses Brazilian household survey data to estimate the impact of fathers' and mothers' education on the labor market status and school attendance of their sons and daughters separately. Bargaining models assume that household allocation outcomes reflect a bargaining process in which household members seek to allocate the resources they control to the goods that they individually prefer. 2 As male and female household heads may have different preferences in general, and different specific preferences for the outcomes for their children depending on the gender of the child, the allocation of resources within a household can be seen as the result of some kind of resolution of the preference differences of the male and female heads. Because the impact of both parents' human capital on the labor status and schooling of children is of primary concern, a sample of observations is used that has complete information on each parent's characteristics, including years of schooling. For example, if the policy goal is to reduce child labor, and child labor is predominantly a male activity in an economy, then the findings suggest that transfers allocated to the father may be more effective in reducing overall child labor than transfers to the mother. From a program effectiveness standpoint, it may be important to determine which parent receives the money, and how much they receive, based on the composition of the family and on the goals of the program.